1994
DOI: 10.1063/1.870479
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of magnetic reconnection during a sawtooth crash in a high-temperature tokamak plasma

Abstract: In this paper a laboratory investigation is made on magnetic reconnection in high-temperature Tokamak Fusion Test Reactor (TFTR) plasmas [Plasma Physics and Controlled Nuclear Fusion Research 1986 (International Atomic Energy Agency, Vienna, 1987), Vol. 1, p. 51]. The motional Stark effect (MSE) diagnostic is employed to measure the pitch angle profile of magnetic field lines, and hence the q profile. An analytical expression that relates pitch angle to q profile is presented for a toroidal plasma with circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
133
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(143 citation statements)
references
References 25 publications
9
133
1
Order By: Relevance
“…Simultaneously, a rapid reflux of thermal energy occurs through the reconnection region along newly connected field lines which connect the inside and the outside of q = 1 surface (Lichtenberg, 1984). The precipitous drop of the pressure gradient, which occurs within a short period of 100-200 µsec τ Sweet−P arker removes the free energy to drive the kink instability, inhibiting the full reconnection process proposed by Kadomtsev. Similar changes of central q values were measured in the sawtoothing plasmas of circular cross section tokamaks by two groups (Soltwisch, 1988) and (Levinton et al, 1993;Yamada et al, 1994;Nagayama et al, 1996). Although the final values of the central q after the crash are different, all reported ∆q < 0.1 during sawteeth.…”
Section: A Sawtooth Reconnection In Tokamakssupporting
confidence: 56%
See 2 more Smart Citations
“…Simultaneously, a rapid reflux of thermal energy occurs through the reconnection region along newly connected field lines which connect the inside and the outside of q = 1 surface (Lichtenberg, 1984). The precipitous drop of the pressure gradient, which occurs within a short period of 100-200 µsec τ Sweet−P arker removes the free energy to drive the kink instability, inhibiting the full reconnection process proposed by Kadomtsev. Similar changes of central q values were measured in the sawtoothing plasmas of circular cross section tokamaks by two groups (Soltwisch, 1988) and (Levinton et al, 1993;Yamada et al, 1994;Nagayama et al, 1996). Although the final values of the central q after the crash are different, all reported ∆q < 0.1 during sawteeth.…”
Section: A Sawtooth Reconnection In Tokamakssupporting
confidence: 56%
“…This was evidenced by the small changes in the q profile which were documented by (Levinton et al, 1993;Yamada et al, 1994;Nagayama et al, 1996). This change of q value represents magnetic reconnection.…”
Section: Magnetic Reconnection In Tokamaksmentioning
confidence: 97%
See 1 more Smart Citation
“…In the situations where magnetic energy is abundant, explosive phenomena such as magnetospheric substorms and solar flares are thought to be driven by this dynamical process [1,2]. Magnetic reconnection also plays an important role in determining the relaxation, stability and transport properties of laboratory fusion plasmas [3][4][5][6]. This process involves the breaking and reconnecting of magnetic field lines in a narrow "diffusion region" where the ideal plasma "frozen-in" condition is violated.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the sawtooth instability was first observed in 1974 [5], the process by which this periodic collapse of the core plasma temperature occurs is still only partially understood. Detailed diagnosis of the sawtooth crash has shown that the temperature profile is initially essentially axisymmetric, but is then deformed by a helical instability before a very rapid temperature collapse re-establishes an axisymmetric profile with a lower value at the magnetic axis [6,7].Tokamak plasmas are susceptible to sawtooth oscillations when the safety factor, q = rB φ /RB θ is less than unity [8], where r, R are the minor and major radii and B φ , B θ are the toroidal and poloidal magnetic fields. The helical perturbation which arises during the crash has an m = n = 1 structure, where m, n are the poloidal and toroidal periodicity of the wave.…”
mentioning
confidence: 99%